Bacterial Endophyte Inhabiting Durio zibethinus and its Radical Scavenging and Antidiabetic Potential - Chigurupati, Sridevi; Vijayabalan, Shantini; Palanimuthu, Vasanth Raj; Das, Suprava; Bhatia, Saurabh (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Endophytes, markedly receiving interest and has been detected to be remarkable sources of bioactive metabolites. Endophytes, which are also called as endosymbionts have pulled into consideration in the discovery for novel bioactive compounds that can be utilized as new medications. In the current study, endophyte has been isolated from Durio zibethinus leaves. 16s rRNA partial genome sequencing was used to identify selected endophyte and the obtained bacterial endophytic crude extract (DZLM) was subjected for the antioxidant and antidiabetic investigations. Results: Cronobacter sakazakii was identifies as the endophye. Qualitative phytochemical test on DZLM confirmed the presence of phenols, carbohydrates, alkaloids, flavonoids, steroids, mucilage, and glycosides. The antioxidant assay of DZLM showed the good antioxidant potency with IC50±SEM: 161±0.08 µg/mL for DPPH assay and IC50±SEM: 126± 0.09 µg/mL for ABTS assay. Antidiabetic assay results demonstrated a dose-dependent percentage inhibition of the enzymes. The results revealed good inhibition of α-amylase with IC50±SEM: 239±0.08µg/mL and α-glucosidase inhibition with IC50±SEM: 241±0.08 µg/mL for DZLM compared to the standard drug, acarbose. Conclusion: The study uncovered the fact that DZLM has a wellspring of natural source of antioxidant and antidiabetic agents and further studies are required for fractionation of the active constituents existing in DZLM and also their structural elucidation which supports the application of endo-symbionts as the basis of future natural medicines.
Keywords: Cronobacter sakazakii; Durio zibethinus; Endophytes; α-amylase; α-glucosidase